Literature Review of Pandemic covid 19 Effects on Employee Compensation - Safuan Safuan; Tedi Kurnia (Journal of Business and Management Review, 2021)
This article aims to determine the development of research on compensation during the Covid 19 pandemic in Indonesia. The method used is a qualitative method by conducting a literature study or literature review. The application used for the literature study is google scholar with the keyword "Covid 19 pandemic compensation". The results of the survey found nine articles regarding compensation. The results of this article's analysis indicate that studies regarding payment during the Covid 19 pandemic are studies of the effect of compensation on employee motivation, employee satisfaction, and employee performance variables. Financial compensation has a dominant variable in influencing employee motivation. During the Covid 19 pandemic, companies asked to maintain employee motivation by providing monetary compensation according to their workload.